(untitled) (Annals of Medical Research, 2024)
Aim: Brain MRI findings in sinus vein thrombosis (SVT) have been well described in many studies. However, to our knowledge, there is no diffusion tensor imaging (DTI) study in these cases in the literature. The main purpose of this article is to examine white matter integrity in SVT and to better understand the possible underlying white matter damage. Materials and Methods: Our retrospective study is a neuroimaging study including 1.5 T MRI and brain DTI to evaluate the white matter integrity of patients with SVT and healthy controls. White matter DTI abnormalities were evaluated according to ROI. DTI findings of cases and healthy controls were compared. Results: In cases with SVT, higher apparent diffusion coefficiency (ADC) values ​​were detected in middle cerebellar peduncle, optic radiatio compared to healthy controls. Decreased fractional anisotrophy (FA) values ​​were detected in cingulum, corona radiata, corpus callosum splenium, anterior limb of internal capsule, posterior limb of internal capsule, optic radiatio and corticospinal tract. High radial diffusivity (RD) values ​​were detected in cingulum, corona radiata, superior longitudinal fasciculus, anterior limb of internal capsule, posterior limb of internal capsule, middle cerebellar peduncle, optic radiatio and corticospinal tract. Low axial diffusivity (AD) values ​​were detected in cingulum, posterior limb of internal capsule and corticospinal tract. Conclusion: Our findings may suggest intercellular edema and axon and myelin damage in white matter tracts in sinus thrombosis. DTI findings may be useful in quantitatively monitoring the response to treatment.